Student-Centered Learning from the Perspective of the Prophet’s Hadith - Alfa Munayah HRP; Muhammad Royyan Faqih Azhary; Maulanida (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study discusses the application of Student Centered Learning (SCL) from the perspective of the Prophet Muhammad's hadith through a thematic study of the book Asbab al-Wurud by Imam Jalaluddin as-Suyuthi. The background of this research is the difficulties experienced by educators in Indonesia in implementing the SCL approach mandated by the government, as well as the author's belief that understanding the Prophet's educational process with his companions can overcome these difficulties. This study aims to identify the hadiths in the book Asbab al-Wurud that represent SCL, assess their quality, and classify the types of the Prophet's educational methods related to SCL. This research is a library research with the primary data source being the book Asbab Wurud al-Hadits by as-Suyuthi. Data collection techniques used the documentation method, while data analysis was conducted through hadith takhrij, sanad and matan quality assessment, and pedagogical analysis. The results showed that out of 96 hadiths contained in the book Asbab al-Wurud, there were 20 hadiths (20.8%) in the full SCL category, 22 hadiths (22.9%) in the semi-SCL category, and 56 hadiths (58.3%) in the non-SCL category. Of the 20 hadiths in the full SCL category, the majority are of sahih or hasan quality. The Prophet Muhammad is proven to have used four main types of SCL, namely Problem Based Learning, Case Based Learning, Contextual Based Learning, and Collaborative Learning. This study also finds that the Prophet's educational model cannot be reduced to a single pedagogical label, but rather is an adaptive pedagogy that is flexible and context-responsive, considering the nature of the material, the needs of learners, and educational goals. This research provides historical and theological legitimacy for the implementation of SCL in Islamic educational institutions, while inviting educators to transcend artificial dichotomies between SCL and TCL and to actualize the Prophetic methodological flexibility.